THE GOOD LIFE AS A “WEALTH” OF NATIONS - Ramírez Gallegos, René (2013)
Based in a criticizes orthodox economics, this article proposes the construction of the notion of the socio-ecology of “Buen Vivir”, in which the unit of value and of analysis is time, instead of money. Whereas the neoclassical paradigm has focused on the production of goods for the maximization of utility, the socio-ecology of Good Living pursuits the generation and satisfaction of relational goods: love, friendship, public participation, work in which there is no division between the world of work and the world of life and the relationship between human beings and nature.